Universal design for learning based on augmented reality to enhance spatial and cognitive engagement of neurodivergent students in an inclusive classroom environment - Aulia Dea Fadzila; Hilal Darmawan (Asian Journal Collaboration of Social Environmental and Education, 2026)
Background: Inclusive education requires learning approaches that can accommodate the diverse cognitive, behavioral, and sensory needs of neurodivergent students, particularly learners with Autism Spectrum Disorder (ASD) and Attention Deficit Hyperactivity Disorder (ADHD). However, conventional classroom instruction often relies on verbal explanation and two-dimensional visual materials, which may limit students’ spatial understanding, sustained attention, memory retention, and active participation. Although Augmented Reality (AR) has been increasingly applied in educational settings to enhance visualization and interactivity, its integration with Universal Design for Learning (UDL) principles to support neurodivergent students in inclusive classrooms remains insufficiently explored. This study investigates the implementation of a UDL-based AR learning model to enhance spatial and cognitive engagement among students with ASD and ADHD in an inclusive classroom environment. Methods: A mixed-methods approach was employed by combining pretest–posttest assessment, classroom observation, and semi-structured teacher interviews. The participants consisted of ten neurodivergent students, including five students with ASD and five students with ADHD, and two inclusive classroom teachers. Findings: Quantitative findings showed improvements across five indicators: spatial recognition, spatial reasoning, cognitive focus, memory retention, and problem-solving accuracy. The highest improvement was found in spatial recognition, followed by problem-solving accuracy and spatial reasoning. Qualitative findings indicated that AR–UDL supported differentiated instruction, increased students’ attention, and encouraged more active interaction during learning activities. However, teachers also reported challenges related to classroom management, students’ overexcitement, and technical readiness. Conclusion: These findings suggest that AR–UDL can serve as a practical and inclusive pedagogical model for supporting neurodivergent learners, especially when implemented with appropriate teacher guidance, ethical consideration, and contextual adaptation. Novelty/Originality of this article: This study contributes empirical evidence to the development of technology-supported inclusive education and provides a foundation for future research involving larger samples, longer intervention periods, and comparative experimental designs.